2009
DOI: 10.1177/0888406409339685
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Teacher Knowledge of Phonemic Awareness and Its Instruction

Abstract: Converging evidence has identified phonemic awareness (PA) as one of five essential components of beginning reading instruction. Evidence suggests that many teachers do not have the recommended knowledge or skills sufficient to provide effective PA instruction within the context of scientifically validated reading education. This study examines the knowledge of PA instruction of 223 first-year teachers initially certified in special education, early childhood education, and elementary education. Results indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 28 publications
1
29
0
3
Order By: Relevance
“…When assessed, teacher candidates (Bos et al, 2001;Washburn, BinksCantrell, Joshi, Martin-Change, & Arrow, 2015), inservice teachers (Bos et al, 2001;Cheesman, McGuire, Shankweiler, & Coyne, 2009), and university-level reading instructors (Joshi et al, 2009) have demonstrated gaps in knowledge of basic language constructs such as phonological awareness, phonemic awareness, alphabet knowledge, phonics, and morphology. Limitations have been found in relation to conceptual knowledge (e.g., understanding of the alphabetic principle) and specific skills (e.g., the ability to identify phonemes within words).…”
Section: Teacher Knowledge Of Phoneme-grapheme Correspondencementioning
confidence: 97%
“…When assessed, teacher candidates (Bos et al, 2001;Washburn, BinksCantrell, Joshi, Martin-Change, & Arrow, 2015), inservice teachers (Bos et al, 2001;Cheesman, McGuire, Shankweiler, & Coyne, 2009), and university-level reading instructors (Joshi et al, 2009) have demonstrated gaps in knowledge of basic language constructs such as phonological awareness, phonemic awareness, alphabet knowledge, phonics, and morphology. Limitations have been found in relation to conceptual knowledge (e.g., understanding of the alphabetic principle) and specific skills (e.g., the ability to identify phonemes within words).…”
Section: Teacher Knowledge Of Phoneme-grapheme Correspondencementioning
confidence: 97%
“…G. Reid Lyon (1998), an expert on reading and the former chief of the Child Development and Behavior Branch within the National Institute of Child Health and Human Development (NICHD) at the National Institutes of Health (NIH), lists four reasons that reading failure continues to persist: lack of phonemic awareness, low comprehension, lack of motivation, and the classroom teaching approach. The classroom teaching method and lack of phonemic awareness have been highlighted by several researchers as two of the root causes of reading failure (Chessman et al 2009;National Reading Panel 2000;. Notice that we did not say classroom teachers were the problem; we said classroom teaching methods-the curriculum and teaching approach being used.…”
Section: First Stage Of Adjustment For Change: Identify the Root Causmentioning
confidence: 82%
“…They must have a thorough understanding of the linguistic structures beyond simple letter -sound correspondences, in addition to the knowledge of difÞculties that students encounter in phonological awareness and word-reading skills (McCutchen et al, 2002). According to Cheesman, McGuire, Shankweiler, and Coyne (2009), special educators need a deeper level of understanding of phonemic awareness than general educators have to provide effective instruction to students who do not respond to classroom instruction. Denton, Vaughn, and Fletcher (2003), too, emphasized the importance of effective and knowledgeable teachers-the Þrst area that must be addressed in an attempt to improve the reading development of all students.…”
Section: Ball State Universitymentioning
confidence: 98%